MIDWIFERY CARE MANAGEMENT FOR NEWBORN BABY MRS. F WITH ASPHYXIA AT SALBIYANA PRIMARY CLINIC - Nisa, Khairun; Nainggolan, Citra Oktavia; Hanim, Humaida; Khairunnisa Situmorang; Salbiyana (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Neonatal asphyxia is a critical condition in newborns caused by the failure to initiate and maintain spontaneous breathing immediately after birth. This condition leads to hypoxia, hypercapnia, and metabolic acidosis. Globally, neonatal asphyxia remains one of the leading causes of neonatal mortality and requires interventions.Objective: This study aimed to implement and evaluate comprehensive midwifery care management for Baby Mrs. F with moderate neonatal asphyxia at Salbiyana Primary Clinic, Deli Serdang Regency.Methods: This study employed a descriptive case study design using Varney’s seven-step midwifery management approach. The stages included basic data collection, data interpretation, identification of potential diagnoses, anticipation of immediate actions, planning, implementation of interventions, and clinical evaluation. Data were collected through direct observation, physical examination, and review of medical records.Results: At birth, the infant presented with signs of moderate asphyxia characterized by central cyanosis, weak muscle tone, slow respiration (30 breaths/minute), and an initial APGAR score of 6 due to a triple nuchal cord complication. Immediate resuscitation procedures were performed according to standard protocols, including positioning the head in slight extension, clearing the airway, drying the infant under an infant warmer, providing tactile stimulation, and ensuring positive pressure ventilation. Following intervention, the infant’s nificantly, with stable respiration (40–60 breaths/minute), heart rate above 100 beats/minute, pink skin coloration, stronger reflexes, and an APGAR score increasing to 7–8 at the fifth minute without secondary complications.Conclusion: The implementation of midwifery management based on Varney’s seven-step approach proved highly effective in managing moderate neonatal asphyxia. Early detection, prompt standardized resuscitation.